Surface Quality of Carbide Metal After Electrical Discharge Machining - Straka, Ľuboslav; Kuchta, Patrik (International Journal of Engineering and Management Sciences, 2023)
Recently, the requirements for machining shape-complex products made of hard-to-machine materials, including carbide, have been increasing significantly. However, their machining is rather problematic. Additionally, a high-quality standard of the machined surface is generally required, not only in terms of roughness but also in terms of the geometric accuracy of the machined surface. All this while maintaining a high level of economy in the machining process. However, meeting these demanding requirements in real technical practice is not always an easy task. Moreover, in combination with modern machining processes, only a limited number of production technologies can meet this requirement. Therefore, due to the high demands placed on today’s modern production and the required high standard of the machined surface, progressive EDM technology is increasingly finding its application. And it is through this progressive technology that it is possible to achieve relatively good success in carbide machining. The aim of this paper was therefore to describe in detail the results of an experimental investigation aimed at identifying the quality of the machined surface achieved in terms of the roughness parameters of the machined surface in the electrical discharge machining of selected types of carbides using a wire tool electrode.